Talent Management Efficiency in Succession Planning: A Proposed Model for HEIs of Pakistan - Khokhar, Rashid Ali; Mangi, Muhammad Saleem; Shah, Muneer Ahmed (Annals of Human and Social Sciences, 2024)
The core objectives of the study are to determine the impact of employee ability on succession planning, the impact of employee motivation on succession plannig, and the impact of training and development on succession planning. Researchers have defined talent management in various ways, including as a process, a competitive advantage, and a means to contribute to overall organizational effectiveness. Assessing employee abilities, employee motivation, and training and development plays a crucial role in succession planning, as it aims to identify and develop potential future leaders within an organization. This research adopted the mixed approach. The qualitative approach is used to analyze the descriptive data while quantitative approach is used to quantify the statistical data. This research adopted the thematic as well as the HEI model to analyse the data secondary sources of data for this research. The findings show an impact of talent management on succession planning. Study shows that talent management is in succession planning. The institution of Higher Education Commission (HEC) should fill this gap.